"Summer is you": Adolescents and young adults with cancer sing about their desire for summer. Issue 5 (24th January 2019) - Signoroni, Stefano; Veneroni, Laura; Pagani Bagliacca, Elena; Gaggiotti, Paola; Silva, Matteo; Casanova, Michela; Chiaravalli, Stefano; Clerici, Carlo Alfredo; Massimino, Maura; Ferrari, Andrea
Abstract: Creative spirit and art are used as part of the Youth Project in Milan, a program dedicated to adolescents and young adults (AYA) with cancer. The "Summer is you" music project involved 45 patients (15–26 years old): with professional help, the patients wrote music and lyrics, sang their song, and recorded a video clip, sharing with us not only their hopes and fears, but also their romantic encounters and their urge to travel (https://youtu.be/Q5FSCMUVg0E ). This project exploited the power of music to bring young people with cancer together in a novel form of support that can complement the more conventional psychological approaches.